RI 3316 Petroleum Engineering Report, Big Spring Field And Other Fields In West Texas And Southeastern New Mexico - In Cooperation With The Chamber Of Commerce, Midland, Texas. ? Introduction - Charles B. Carpenter (The National Institute for Occupational Safety and Health (NIOSH), 1936)
In general terminology, the West Texas Permian Basin comprises the area south of the Texas Panhandle and west of the Bend Arch or Central Basin region. It is outlined mere definitely by geologists, however, as that area underlain by the south half of the Permian Salt Basin4/ and includes Scurry, Mitchell, Sterling, Howard, Glasscock, Reagan, Crockett, Upton, Midland, Martin, Gaines, Andrews, Ector, Crane, Pecos, Ward, Winkler, and Loving Counties in Texas, and Lea and Eddy Counties in New Mexico. The oil fields of the area, of which more than 70 have been discovered, are shown in fire 1. Approximately 4,200 producing oil wells have been drilled in these fields. Oil has been produced from limestones and dolomites of Permian age in most of the fields in the West Texas Permian Basin. Some of the fields produced oil from sandstone beds above the limestone, and in two fields production has been found below the limestone in formations of Ordovician age.